2016
DOI: 10.1590/2237-6089-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Main mental disorders in crack-cocaine users treated at Psychosocial Care Centers for Alcohol and Drugs in the city of Recife, Brazil

Abstract: Data from this study showed strong associations between crack-cocaine uses and development of mental disorders, particularly when abuse of multiple substances occurs. Based on these data, there is a clear need for coordination of related public policies for support and social reintegration to provide these people with comprehensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
1
0
4
Order By: Relevance
“…The prevalence of crack cocaine users undergoing treatment in this study (47%) is similar to those observed in other studies. A previous study that evaluated the demand of crack cocaine users under treatment at the Psychosocial Support Center -Alcohol and Drugs (CAPS AD) -a service with similar characteristics that also offers multi-professional outpatient care, found a similar prevalence rate (45%) 20 . Whereas the prevalence of psychiatric hospitalization was 21.6% 21 and attendance of therapeutic communities was 92.3% 22 .…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of crack cocaine users undergoing treatment in this study (47%) is similar to those observed in other studies. A previous study that evaluated the demand of crack cocaine users under treatment at the Psychosocial Support Center -Alcohol and Drugs (CAPS AD) -a service with similar characteristics that also offers multi-professional outpatient care, found a similar prevalence rate (45%) 20 . Whereas the prevalence of psychiatric hospitalization was 21.6% 21 and attendance of therapeutic communities was 92.3% 22 .…”
Section: Discussionmentioning
confidence: 93%
“…Uma das demandas mais significativas para os SE são os transtornos psiquiátricos, que tem elevada prevalência na população (3) . Isto pode estar relacionado à epidemia de dependência de álcool e outros transtornos relacionados ao uso de drogas, evidenciando a necessidade de abranger o atendimento desses casos, no sistema de saúde (4) . Em muitos países, incluindo o Brasil, os Serviços de Emergência, frequentemente, são o primeiro contato desses indivíduos com o sistema de saúde e/ou a principal fonte de encaminhamento para o tratamento (5,6) .…”
Section: Introductionunclassified
“…As características da amostra de dependentes de crack utilizada no nosso estudo são condizentes com o perfil de usuários relatado nesses estudos, podendo ser considerada como representativa dessa população. Apesar de a nossa amostra ser proveniente de um estudo com usuários de crack internados para tratamento em comunidades terapêuticas, as características da amostra também são similares aos perfis descritos para dependentes de crack em tratamento, como em comunidades terapêuticas 136,138,139 , hospitais psiquiátricos e serviços ambulatoriais 66,137,[140][141][142][143] .…”
Section: Objetivo Específicounclassified
“…A presença de um segundo diagnóstico psiquiátrico é comum entre usuários de cocaína e crack e pode aumentar a gravidade de ambas as doenças 134 . Os transtornos mais prevalentes relacionados à dependência de crack são os transtornos de humor, como a ansiedade e a depressão 66,74,138,139,142,188,189 , sendo esse último também relacionado como um sintoma secundário ao consumo da droga 76 . Diante desse cenário, consideramos a importância de avaliar os dependentes de crack da nossa amostra em relação a exposição à eventos traumáticos e a presença de depressão, ansiedade e outros transtornos psiquiátricos.…”
Section: Objetivos Específicos 3 Eunclassified